2020
DOI: 10.1136/lupus-2019-000362
|View full text |Cite
|
Sign up to set email alerts
|

Similar progression of carotid intima–media thickness in 7-year surveillance of patients with mild SLE and controls, but this progression is still promoted by dyslipidaemia, lower HDL levels, hypertension, history of lupus nephritis and a higher prednisolone usage in patients

Abstract: ObjectiveTo compare progression of subclinical atherosclerosis and factors promoting it in patients with SLE and controls.MethodsConsecutive patients with SLE and age-matched, sex-matched population controls from the SLEVIC cohort were assessed at inclusion and after 7 years with standardised data collection and carotid ultrasound. Effect of risk factors on carotid intima–media thickness (cIMT) progression was examined with adjusted linear mixed models.ResultsA total of 77 patients and 74 controls, 68% and 61%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
0
23
1
Order By: Relevance
“…We have, however, shown similar cIMT progression over 7 years in patients with mild SLE and the controls. 43 Carotid plaques could be a stronger marker of atherosclerotic vessel disease and a predictor of clinical events, when compared with cIMT. Interestingly, the plaque progression rate was higher than, and the intima-media thickness progression rate was similar to, those in the control group in the Pittsburgh lupus cohort.…”
Section: Discussionmentioning
confidence: 99%
“…We have, however, shown similar cIMT progression over 7 years in patients with mild SLE and the controls. 43 Carotid plaques could be a stronger marker of atherosclerotic vessel disease and a predictor of clinical events, when compared with cIMT. Interestingly, the plaque progression rate was higher than, and the intima-media thickness progression rate was similar to, those in the control group in the Pittsburgh lupus cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies used US in SLE for both risk assessment and follow-up ( 33 ), but several studies have focused mainly on IMT and the presence of plaques seen in CCA ( 3 , 34 , 35 ). Sporadic studies have evaluated the benefit of US in other vessels ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to estimate accumulated life-time intake of glucocorticoids, but most patients were in quiescent phase of their disease on a stable dose of steroids during the last 6 months. Ajeganova et al observed progression of IMT in CCA among patients with SLE during a 7-year surveillance and showed that traditional risk factors, LN, and higher doses of corticosteroids were associated with the progression of IMT ( 33 ). By comparing the phenotypic subgroups and controls, we found that IMT of ICA, CFA, and the aortic arch was higher in the APS group.…”
Section: Discussionmentioning
confidence: 99%
“…Falashi et al evaluated twenty-six cSLE patients and reported that patients with nephrotic-range proteinuria have significantly higher CIMT than those without proteinuria [ 4 ]. History of lupus nephritis and hypertension were correlated with CIMT in a seven-year surveillance in another SLE study that showed no difference in progression of subclinical atherosclerosis between patients with mild lupus and control subjects [ 49 ]. On the other hand, Sharma et al reported no significant differences in CIMT between 102 SLE patients with and without nephritis, although the nephritis group exhibited a higher SLEDAI score, more persistent inflammation and, consequently, higher risk to developed arterial injury leading to early end-organ damage [ 50 ].…”
Section: Discussionmentioning
confidence: 99%